2022
DOI: 10.1063/5.0105337
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical response and vibrational resonance of a tri-stable energy harvester interfaced with a standard rectifier circuit

Abstract: This paper investigates the dynamical response and vibrational resonance (VR) of a piecewise electromechanically coupled tri-stable energy harvester (TEH), which is driven by dual-frequency harmonic excitations. To achieve a stable DC output, the TEH is interfaced with a standard rectifier circuit. Using the harmonic balance method combined with the separation of fast and slow variables, a steady-state response together with the analytical expressions of displacement and harvested power is derived. The multi-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…To that end, numerous multi-stable devices have been designed for harvesting energy from vibrations in several application sectors, such as infrastructure [4], [5], medical, wearables to mention a few, while extensive literature reviews provide a detailed overview of the reported research and development in the field [3], [6]. The functional principle of a large part of these nonlinear devices is based on electromagnetic forces acting on a cantilever beam carrying piezoelectric transducers [7] connected to harvesting circuits [8]. Another popular relevant physical concept is the exploitation of the bistable response of a post-buckled piezoelectric beam subjected to base excitation [9].…”
Section: Introductionmentioning
confidence: 99%
“…To that end, numerous multi-stable devices have been designed for harvesting energy from vibrations in several application sectors, such as infrastructure [4], [5], medical, wearables to mention a few, while extensive literature reviews provide a detailed overview of the reported research and development in the field [3], [6]. The functional principle of a large part of these nonlinear devices is based on electromagnetic forces acting on a cantilever beam carrying piezoelectric transducers [7] connected to harvesting circuits [8]. Another popular relevant physical concept is the exploitation of the bistable response of a post-buckled piezoelectric beam subjected to base excitation [9].…”
Section: Introductionmentioning
confidence: 99%